Pattern of Bone Mineral Density In Postmenopausal Women in a Tertiary Care Centre of Bangladesh - Halder , Durba; Ali, Md Yousuf; Faysal , Janesar Rahat; Nayeem, Farhana; Rouf , Abdur; Tasnim, Nabeela (Bangladesh Journal of Medicine, 2023)
Background: Incidences of osteoporosis and diabetes have dramatically increased in recent decades and they have become one of the major health problems.Osteoporosis is a skeletal condition characterized by decreased density (mass/volume) of normally mineralized bone. The reduced bone density leads to decreased mechanical strength, thus making the skeleton more likely to fracture. This study aimed to assess the pattern of bone mineral density in Bangladeshi postmenopausal women. Methods: This descriptive cross-sectional study was conducted at the Department of medicine, Sir Salimullah Medical College, Mitford, Dhaka, Bangladesh. The study duration was 1 year; from January 2021 to January 2022. A total of 100 women attending the Outpatient Department of Medicine were included in this study as per inclusion criteria. A convenience sampling technique was applied for this study.A pre-formed questionnaire was used for necessary data collection containing general characteristics, presence or absence of risk factors, BMI status, and BMD. Qualitative data were analyzed by Chi-square test & quantitative data were analyzed by student’s t-test. All statistical analyses were performed by using SPSS Software version 20. Informed written consent was obtained from all subjects. Results: In this study, a maximum (of 36, 36.0%) patients belonged to the age group of 50-59 years, followed by (33, 33.0%) 60-69 years age group. Regarding education, most patients (70, 70.0%) had a secondary school certificate or below that level, followed by higher secondary level (25, 25.0%). Concerning years since menopause, 27.0% of patients had menopause since 20-29 years, followed by 25.0% of subjects had menopause since 10-19 years.Regarding BMI, 20.0% of patients had <23 kg/m2, 24.0% 23.1-25.99 kg/m2, 25.0% 26-29.99 kg/m2, and 31.0% ≥30 kg/m2.Concerning risk factors, 45.0% of patients had a history of taking medication containing estrogen, 40.0% of patients had DM, and 18.0% of patients had a history of taking thyroid hormone.Prevalence of osteopenia and osteoporosis was seen in 33.0% and 8.0% of patients respectively concerning BMD proximal femur and spine DXA. Moreover, concerning DXA at the lumbar spine, hip, and total body osteopenia and osteoporosis were 50.0% and 30.0% respectively. Conclusion: This study suggests that advancing age and menopausal condition are an important risk factor for the occurrence of low BMD. Bangladesh J Medicine 2023; 34(2): 121-125